Heterogeneous nickel isotopic compositions in the terrestrial mantle - part 1: ultramafic lithologies - Saunders, NJ; Barling, J; Harvey, J; Halliday, AN (Elsevier, 2020)
High precision nickel stable isotopic compositions (δ60/58Ni) are reported for 22 peridotite xenoliths from the USA (Kilbourne Hole, New Mexico), Tanzania, and Cameroon. For a subset of these, δ60/58Ni is also reported for their constituent mineral separates (olivine, orthopyroxene, clinopyroxene, and spinel). Bulk peridotites show significant heterogeneity in Ni isotopic composition, ranging from +0.02‰ to +0.26‰. Unmetasomatised fertile peridotites from three localities, define an average δ60/58Ni of +0.19±0.09‰ (n = 18). This value is comparable to previous estimates for the δ60/58Ni of the bulk silicate earth (BSE), but is unlikely to be representative, given observed heterogeneity, presented here and elsewhere. Samples with reaction rims and interstitial glass (interpreted as petrographic indications of minor metasomatism) were excluded from this average; their Ni isotopic compositions extend to lighter values, spanning nearly the entire range observed in peridotite worldwide. Dunites (n = 2) are lighter in δ60/58Ni than lherzolites and harzburgites from the same location, and pyroxenites (n = 5) range from +0.16‰ to as light as −0.38‰. The δ60/58Ni in the Kilbourne Hole xenoliths correlate negatively with bulk-rock Fe concentration and positively with 143Nd/144Nd, providing evidence that light δ60/58Ni is associated with mantle fertility and enrichment. The trend between δ60/58Ni and Fe concentration in bulk rocks appears to be global, replicated across the peridotites in this work from other localities, and in literature data. The inter-mineral fractionations are small; the maximum difference between heaviest and lightest phase is 0.12‰. This provides evidence that bulk rock δ60/58Ni variation does not result from differences in modal mineralogy, fractional crystallization or degrees of partial melting. The δ60/58Ni fractionation appears to be an equilibrium effect and usually is in the decreasing order spinel > olivine = orthopyroxene > clinopyroxene. However, the fractionation between clinopyroxene and orthopyroxene varies in magnitude and sign, and is correlated with pyroxene Si/Fe positively, and Fe/Mg negatively. The magnitude of inter-pyroxene fractionation also correlates with other pyroxene compositional ratios (e.g. La/Smclinopyroxene); as well as bulk rock δ60/58Ni, and [U]. These data provide evidence that Ni isotopes fractionate at the bulk rock and mineral scale in response to mantle enrichment processes, possibly related to recycling of isotopically light subducted components.